Rousseau, Robespierre, and English Romanticism - Dart, Gregory (Cambridge studies in Romanticism, 1999)
This book re-opens the question of Rousseau's influence on the French Revolution and on English Romanticism, by examining the relationship between his confessional writings and his political theory. Gregory Dart argues that by looking at the way in which Rousseau's writings were mediated by the speeches and actions of the French Jacobin statesman Maximilien Robespierre, we can gain a clearer and more concrete sense of the legacy he left to English writers. He shows how the writings of William Godwin, Mary Wollstonecraft, William Wordsworth and William Hazlitt rehearse and reflect upon the Jacobin tradition in the aftermath of the French revolutionary Terror.